De rol van de Schelde in het Romeins transportsysteem (50 v.Chr. - 410 n. Chr.). - BONGERS, Toon (Handelingen- Koninklijke Zuidnederlandse Maatschappij voor Taal- End Letterkunde en Ges, 2019)
Archaeological sources make it impossible to deny that rivers served as pathways in the past. Conversely, the role of inland waterways in the Roman transport economy of northern Gaul has received little scholarly attention. This paper introduces a historicalarchaeological study of the transport network of the Roman-era Scheldt basin (presentday north-western Europe), with an emphasis on the role of waterways. As a starting point, this study works from the hypothesis of an integrated transport network, in which rivers, roads, and seaways link up to form a single system.